Genetic Polymorphisms as Predictive Markers of Response to Growth Hormone Therapy in Children with Growth Hormone Deficiency - Jung, Anna Maria; Zenker, Martin; Lißewski, Christina; Schanze, Denny; Wagenpfeil, Stefan; Rohrer, Tilman Robert (Klinische Pädiatrie, 2017)
Objective Growth hormone (GH) deficiency (GHD) is commonly treated with recombinant human GH (rhGH). Individual response to rhGH therapy varies widely and there is evidence that variations in growth-related genes, e. g. the GH receptor (GHR) gene, may impact treatment response. We aimed to identify genetic polymorphisms which could serve as predictive markers of response to rhGH therapy.Methods We conducted a genetic analysis of single nucleotide polymorphisms (SNPs) and the GHR exon 3 deletion in 101 paediatric GHD patients receiving rhGH. Patients were analysed for 13 known SNPs in 11 genes of the GH axis (SOS1, IGFR1, GAB1, LHX4, IGFBP3, GRB10, GHRHR, GHSR), growth plate (VDR, ESR1) and cell cycle (CDK4). Individual index of responsiveness (IoR) values were compared by genotype. We also analysed the potential association between the IoR and the GHR exon 3 deletion. IoRs were analysed by genotype by one-way analysis of variance and unpaired t-test.Results Variations in two SNPs, rs2888586 (SOS1) and rs2069502 (CDK4), and the GHR exon 3 deletion were significantly associated with response to rhGH treatment.Conclusions Genetic variations are potentially suitable as predictive markers of rhGH treatment response in GHD. Genetic analysis provides a starting point for individualised treatment of GHD.
Keywords: single nucleotide polymorphism; growth hormone deficiency; treatment response; genetic marker; response prediction